Data from: Cytoplasmic DNA variation and biogeography of Larix Mill. in Northeast Asia - Polezhaeva, Maria; Lascoux, Martin; Semerikov, Vladimir (Zenodo, 2010)
Range-wide variation in 54 populations of Dahurian larch (Larix gmelinii) and related taxa in Northeast Asia was assessed with four mitochondrial PCR-RFLP and five chloroplast SSR markers. Eleven mitotypes and 115 chlorotypes were detected. The highest diversity was observed in the southern Russian Far East where hybrids of L. gmelinii, L. olgensis and L. kamtschatica are distributed. In contrast, only two mitotypes occurred in L. cajanderi and L. gmelinii. The Japanese larch (L. kaempferi) was found to be closely related to populations of L. kamtschatika inhabiting the Kuril Islands and South Sakhalin, populations from the northern part of Sakhalin being more closely related to continental species. In general, both mitochondrial (GST = 0.786; NST = 0.823) and chloroplast (GST = 0.144; RST = 0.432) markers showed a strong phylogeographical structure and evidence of isolation-by-distance. Yet both markers did not allow a clear delineation of species borders. In particular, and contrary to expectations, cpDNA was not significantly better than mtDNA to delineate species borders. This lack of concordance between morphological species and molecular markers could reflect extensive ancestral haplotype sharing and past and ongoing introgression. Finally the distribution of mtDNA and cpDNA variation suggests the presence of several refugia during Pleistocene glacial intervals. In particular, mDNA and cpDNA reveal weak but visible differentiation between L. gmelinii and L. cajanderi suggesting independent glacial histories of these species. Dryad.xls